Evaluation of Ontology Mapping Representations - THOMAS, HENDRIK; BRENNAN, ROB; O'SULLIVAN, DECLAN (My University, 2009)
A common approach to mitigate the effects of ontology heterogeneity is to discover and express the specific correspondences between different ontologies. An open research question is: how should such ontology mappings be represented. In recent years several proposals for an ontology mapping representation have been published, but till today no format is officially standardized or generally accepted in the community. In this paper we will present a new evaluation framework for ontology mapping representations for a pragmatic state of the art overview of their characteristics. In particular we are interested how current ontology mapping representations can support the management of ontology mappings (sharing, re-use, alteration) as well as how suitable they are for different mapping tasks.
Workshop on Matching and Meaning, AISB 2009 Convention
PUBLISHED
Edinburgh
Keywords: Ontology Mapping Representation; Intelligent Content & Communications; Telecommunications